Accidents caused by venomous animals: an analysis of the epidemiological profile in the Northeast region of Brazil in the period from 2010 to 2019 (Research, Society and Development, 2020)
Objective: This research aims to characterize the epidemiological profile of accidents by venomous animals in the Northeast region of Brazil. Methodology: Cross-sectional, descriptive study with a quantitative approach on accidents with venomous animals in the Northeast of Brazil in the period from 2010 to 2019. This research consisted of six stages, where it established well-defined criteria on data collection, analysis, and presentation of results. Qualitative variables were distributed based on the type of animal, sex, age ranges, time elapsed between the bite and the service, case classification, clinical evolution, and notification status. Results: The sample consisted of 607,966 cases distributed in the years collected, with accidents involving female, brown people, young adults between 20 and 39 years old, and the scorpion being the animal most involved in the cases. There was an exponential increase in accidents with venomous animals in all states in the Northeast region, varying between 84.5% and 352.4% between the first and the last year of the study. Piauí showed the greatest variation in the number of cases, but Bahia was the state with the highest number of notifications. The evolution of the cases showed a good indication of cure. Conclusion: It was possible to characterize the epidemiological profile of accidents by venomous animals in the Northeast region of Brazil. Therefore, it has been that these accidents are increasingly increasing, with this it is necessary to develop strategies that can minimize accidents, injuries, and underreporting.